Potential increased propofol sensitivity in cognitively impaired elderly: a controlled, double-blind study - Zhuge, Huiting; Zhou, Yu; Qiu, Yimin; Huang, Xiaojing (Frontiers in Aging Neuroscience, 2024)
Background Cognitive impairment in the elderly may lead to potential increased sensitivity to anesthetic agents targeting receptors associated with cognition. This study aimed to explore the effect of cognitive status on propofol consumption during surgery in elderly patients. Methods Sixty elderly patients scheduled for laparoscopic radical prostatectomy were allocated to either a cognitively normal [CogN, Montreal Cognitive Assessment (MoCA) score ≥26] or cognitively impaired (CogI, MoCA <26) group. Propofol was administered via target-controlled infusion to maintain a bispectral index (BIS) between 55–65 during surgery. Propofol consumption was recorded at three time points: T1 (abolished eyelash reflex), T2 (BIS = 50), T3 (extubation). BIS values at eyelash reflex abolition were also recorded. Postoperative MoCA, Visual Analogue Scale (VAS) scores, and remifentanil/sufentanil consumption were assessed. Results BIS values before induction were similar between CogN and CogI groups. However, at eyelash reflex abolition, BIS was significantly higher in CogI than CogN (mean ± SD: 65.3 ± 7.2 vs. 61.1 ± 6.8, p = 0.031). Propofol requirement to reach BIS 50 was lower in CogI vs. CogN (1.24 ± 0.19 mg/kg vs. 1.46 ± 0.12 mg/kg, p = 0.003). Postoperative MoCA, VAS scores, and remifentanil/sufentanil consumption did not differ significantly between groups. Conclusion Compared to cognitively intact elderly, those with cognitive impairment exhibited higher BIS at eyelash reflex abolition and required lower propofol doses to achieve the same BIS level, suggesting increased propofol sensitivity. Cognitive status may impact anesthetic medication requirements in the elderly.